Symbiosis - Silverstein, Alvin; Silverstein, Virginia B.; Nunn, Laura Silverstein (Brookfield, Conn. : Twenty-First Century Books, 1998)
Discusses the three kinds of symbiosis: mutualism, commensalism, and parasitism and describes examples of these relationships.
Includes bibliographical references (p. 58-60) and index.
Wilson's Junior High School, September 2001
School Library Journal, February 1999
5.5
5-8
Keywords: Symbiosis